Food-based approaches for ensuring adequate vitamin A nutrition - Tanumihardjo, Sherry A. (International Food Policy Research Institute, 2008)
More than 250 million children under the age of five have vitamin A (VA) deficiency. Efforts to improve VA status globally have included supplementation and food fortification. Supplementation, however, can result in sharp spikes and declines in VA concentration in the body, while VA fortificants can lead to hypervitaminosis, which requires continuous monitoring to ensure that levels of total ? body VA are not excessive. Biofortifying staple crops with ??carotene, a major source of provitamin A, is an emerging option for improving VA status without these shortcomings. This review tests the extent to which biofortification may be an alternative to supplementation and food fortification.